Technology enhanced learning for people with disabilities approaches and applications - Ordóñez de Pablos, Patricia 1975-; Zhao, Jingyuan 1968-; Tennyson, Robert D. (Premier reference source, 2011)
"This book brings together academics, policy-makers and practitioners, with the goal of delivering a reference edition for all those interested in approaches and applications of technology enhanced learning for people with disabilities" - Provided by publisher